A new model for sizing thermosiphon solar heating systems (Research, Society and Development, 2020)
The purpose of this work is to present a simple methodology which enables to size a thermosyphon system without always having to resort to a computational simulation. As a result of many system simulations using the TRNSYS software, whereby several project and equipment parameters were varied, a group of expressions were obtained which allow the determination of the system thermal daily efficiency (monthly average). The developed correlation includes geometric and thermal aspects related to the collector, the storage tank and the connecting pipes, as well as operational data such as thermal load, solar radiation and room temperature. This model is able to optimize several variables that comprise thermosyphon solar water-heating systems for the requirements of particular applications. The resulting correlation shows that the efficiency is a linear function of meteorological conditions, collector quality and parameters related to storage tank volume, volume load (consumption profile) and collector area. The correlation is very useful since it is a simple, fast alternative for the calculation of system efficiency without depending on experimental determination or numerical simulation results. The determination and sizing of the collector area and the volume storage tank that satisfy the required thermal load can be appropriately performed in a simple and fast way by using the proposed correlation.